ANALISIS BAURAN PROMOSI PT. NIAGA DIGITAL PERSADA PADA PRODUK FROZEN FOOD JAKARTA DALAM UPAYA MENINGKATKAN PENJUALAN PRODUK TAHUN 2023 - Gustafa, Fikih (Jurnal Pijar, 2024)
Global competition has forced many companies to establish new strategies in order to face competition in several corporate sectors, either by providing information to increase sales. Promotion is one of the sectors experiencing competition. Apart from being used for promotional media, the promotion mix can also be used to increase sales. PT. Niaga Digital Persada or Frozen Food Jakarta is a company in the field of Supplier Distributor. Frozen Food Jakarta is now using Promotion Mix for its marketing activities because it is considered more effective and efficient. Not only for marketing matters, but Frozen Food Jakarta utilizes the Promotion Mix as a means of promotion to increase sales. This study aims to find out what promotion mix is ​​used by PT. Niaga Digital Persada Frozen Food Jakarta in increasing product sales. While the method used in this study is a qualitative descriptive method, with data collection techniques through observation and in-depth interviews with 2 informants who are familiar with the Promotion Mix process at Frozen Food Jakarta. The data analysis technique used in this study is the Miles and Huberman technique. The results of this study are to discuss the problem in depth, the Promotion Mix used by PT. Niaga Digital Persada Frozen Food Jakarta is Advertising, Sales Promotion, Public Relations, Personal Selling. By using the same promotion, Frozen Food Jakarta promotes interesting services and product information so that it can increase the company's sales, and make the Frozen Food Jakarta company grow. The conclusion of this study is that it can be seen that PT. Niaga Digital Persada or Frozen Food Jakarta uses a promotional mix such as advertising, sales promotion, personal selling, public relations to increase sales of the company's products. From the things that have been done, Frozen Food Jakarta has succeeded in increasing sales of its company's products so that Frozen Food Jakarta is increasingly known and growing.